The Library Of Congress, 1st edition - Goodrum, Charles A (Routledge, 2020)
From a review of the first edition: "For those of us whose minds unhinge at the sheer immensity of the Library of Congress, with its maze of corridors, multilayered stacks and circuitous subterranean passages, this study will prevent many a false step."—Smithsonian Since the first edition of this book appeared in 1972, there have been many changes in the Library, including a massive reorganization begun in 1977 under the leadership of Daniel J. Boorstin, the present Librarian of Congress. This completely revised and updated look at the Library brings the story up to date, discussing the Library's history, how it works, how the user can take advantage of its many services, where it is going, and how it meets the wide-ranging needs of Congress, other federal government offices, and the library, scholarly, and creative worlds. The authors emphasize the recent impact of technology on what is the largest information-storage and retrieval "machine" in the world. Lively writing and accessible language make this book an ideal introduction to the Library of Congress for the visitor, the first-time user, or the general reader, but it is also a must for every library and librarian, as well as an excellent textbook for library administration courses. The information it contains will make it of great interest even to the most experienced users of the Library.